Headache patients' satisfaction with telemedicine: a 12-month follow-up randomized non-inferiority trial - Müller, Kai Ivar; Alstadhaug, Karl Bjørnar; Bekkelund, Svein Ivar (European Journal of Neurology, 2017)
Source at https://doi.org/10.1111/ene.13294 . Background and purpose: We investigated non-acute headache patients’ long-term satisfaction with a telemedicine consultation and consultation preferences in northern Norway. We hypothesized that patients were not less satisfied with telemedicine than traditional consultations. We also examined the influence of gender, age and education on satisfaction. Methods: For 2.5 years, patients were consecutively screened, recruited and randomly assigned to telemedicine or traditional visits with a consultation at a neurological outpatient department. The primary endpoint was frequency of satisfied patients at 3 and 12 months. Secondary endpoints were satisfaction with consultation, communication, information, diagnosis, advice and prescriptions, and preferred visit form at 12 months. Results: Of 402 participants, 279 (69.4%) answered questionnaires at both 3 and 12 month, and 291 (72.4%) responded at 12 months. The long-term satisfaction of telemedicine patients was 124/145 (85.5%) compared with 118/134 (88.1%) in the traditional group (P = 0.653). The groups did not differ with respect to secondary endpoints, but females were more satisfied with telemedicine communication (P = 0.027). In the telemedicine group, 99/147 (67.3%) were indifferent to the type of consultation. Age and education did not alter the primary results. Conclusions: At 1 year after a specialist evaluation for headache, telemedicine patients did not express less satisfaction than those with traditional consultation. Telemedicine specialist consultations may be a good alternative for headache patients in secondary care.